Note On Portfolio Optimization An Empirical Study using Bisnis Index-27 and Gold as A Portfolio Asset - Adhiatama, Zenda Christian; Sukarno, Subiakto (The Indonesian Journal of Business Administration, 2012)
The global economic crisis in 2008, which originated in America impacted quite significant for the world economy. Slowing the growth of the economy was felt by some developed countries that are trading partners of the Americas. Exacerbated by this crisis Europe where some European countries have considerable debt and incriminating the economy of the countries. Decrease in the level of economic growth in developed countries, forcing investors to divert its funds shows that yield higher. Indonesia became a new spotlight for investor to invest their fund because of the economic growth and political stability.The emerge of new investment strategy makes investor confuse to choose the appropiate based on their risk profile. Using optimization model that create by Harry Markowitz and the combination of stock and gold as asset portfolio can be an alternative investment strategy for investor. Â Keywords: stocks, gold, IHSG, correlation, modern portfolio, rebalancing